Shifting Learning in to Mobile Learning and Teachers’ Attitude towards it. - Gupta, Nitin Kumar; Vishwakarma, Dr.V.P. (IJRDO- Journal of Educational Research, 2017)
The potential of Mobile phone technology huge and it has broken ground for enhancing knowledge, in higher education. however, it was found that there was lack of academic researches on the use of mobile phone technology for knowledge sharing process in educational system. Today’s teacher must be updated with innovative technology like mobile technology if they want to sustain in the field of education. There is a lack of awareness of mobile learning among most of the teachers in our country. We have written this paper after reviewing some papers related to Mobile learning and it has been found that using Mobile devices in the classrooms scenario and other educational purposes play an important role in enhancing learning. It has also been found that teachers and students have positive attitude towards mLearning in foreign countries and our country also. So researchers’ main objective was to give emphasis on using the mobile devices in our education system.